2020
DOI: 10.1007/s11709-019-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the application of oil palm fibers in cement composites

Abstract: Fibers obtained from different parts of the oil palm tree (Elaeis guineensis) have been under investigation for possible use in construction. Studies have been carried out investigating the engineering properties and possible applications of these fibers. However, the experimental methods employed and the values of mechanical and physical properties recorded by various authors are inconsistent. It has therefore become necessary to organize information which would be useful in the design of oil palm fiber cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 52 publications
(107 reference statements)
1
19
1
Order By: Relevance
“…The compressive strength test (CT) results of LFC specimens of density 600kg/m 3 , 1100kg/m 3 and 1600kg/m 3 respectively are displayed in Figures (8,9 and 10) indicating the test outcomes at 7days, 28days and 56 days. It was found that the compressive strength in all cases increases with age and is in direct correlation with LFC density and layer(s) of confinement in the specimens as supported by the literature [40]. The 56 th day compressive strength of LFC specimens confined with 1L-FGM,2L-FGM and 3L-FGM at 600kg/m 3 density was +58.94%, +137.89% and +168.42% respectively greater than unconfined/control specimens.…”
Section: Compressive Strengthsupporting
confidence: 79%
“…The compressive strength test (CT) results of LFC specimens of density 600kg/m 3 , 1100kg/m 3 and 1600kg/m 3 respectively are displayed in Figures (8,9 and 10) indicating the test outcomes at 7days, 28days and 56 days. It was found that the compressive strength in all cases increases with age and is in direct correlation with LFC density and layer(s) of confinement in the specimens as supported by the literature [40]. The 56 th day compressive strength of LFC specimens confined with 1L-FGM,2L-FGM and 3L-FGM at 600kg/m 3 density was +58.94%, +137.89% and +168.42% respectively greater than unconfined/control specimens.…”
Section: Compressive Strengthsupporting
confidence: 79%
“…Oil palm broom fibres (OPBF) are the ribs of the leaflets of oil palm trees. Studies on OPBF for engineering applications are very few and recent [9,10]. OPBF is presently mainly used as sweeping brooms in many countries around the world.…”
Section: Oil Palm Broom Fibres (Opbf)mentioning
confidence: 99%
“…The leaflets are first detached from the petioles, then the leaves are peeled-off the ribs; herein referred to as OPBF. The fibres are then tied into broom units only to be sold at local markets [9]. Each broom unit consists of between 150-200 individual fibres.…”
Section: Oil Palm Broom Fibres (Opbf)mentioning
confidence: 99%
“…Possible uses of oil palm fibres in construction have been investigated and previous studies have shown possible applications of these fibres [12,15,18,[24][25][26][27][28][29][30][31][32]. Investigations into the engineering properties and possible applications of fibres obtained from different parts of the oil palm tree can also be found [27,33]. Types of oil palm fibres include; Empty fruit bunch fibres (EFBF), frond fibres (OPFF), trunk fibres (OPTF) and broom fibres (OPBF).…”
Section: Oil Palm Fibresmentioning
confidence: 99%